Unusual Presentation of Hepatocellular Carcinoma into Right iliac fossa: A Rare Entity - Uthamalingam, Murali (J Clin Diagn Res, 2015)
Hepatocellular carcinoma (HCC) is the most common primary malignant hepatic tumour. Hepatocellular carcinoma presenting itself or extending into the right iliac fossa (RIF) is a very rare entity. We report on a rare case of hepatocellular carcinoma in a 60-year-old lady, presented with a mobile mass in the lower abdomen without cirrhosis, with normal α-feto protein levels (AFP) or any known risk factors for liver disease. HCC in this case was unusual in its presentation both in the patient as well as a disease.